Estrogenic potency of MC-LR is induced via stimulating steroidogenesis: In vitro and in vivo evidence. (September 2018) - Hou, Jie; Su, Yujing; Lin, Wang; Guo, Honghui; Li, Li; Anderson, Donald M.; Li, Dapeng; Tang, Rong; Chi, Wei; Zhang, Xi
Abstract: Waterborne microcystin-LR (MC-LR) has been reported to disrupt sex hormones, while its estrogenic potency remains controversial. We hypothesized that MC-LR could induce estrogenic effects via disrupting sex hormone synthesis, and verified this hypothesis by in vitro and in vivo assays. Effects of MC-LR (1, 10, 100, 500, 1000 and 5000 μg/L) on steroidogenesis were assessed in the H295R cells after 48 h. The contents of 17β-estradiol (E2) and testosterone (T) increased in a non-dose-dependent manner, which showed positive correlations with the expression of steroidogenic genes. In the in vivo assay, adult male zebrafish were exposed to 0.3, 1, 3, 10 and 30 μg/L MC-LR for 30 d. Similarly, E2 and T contents in the testis were increased, accompanied by extensive up-regulation of steroidogenic genes, especially cyp19a . Meanwhile, the percentage of spermatid in the testis declined. In the liver, the vtg1 gene was significantly up-regulated while both the transcriptional and protein levels of the estrogenic receptor (ER) declined. These results indicate that MC-LR induced non-dose-dependent estrogenic effects at environmental concentrations, which may result from steroidogenesis stimulation via a non-ER-mediated pathway. Our findings support a paradigm shift in the risk assessment of MC-LR from traditional toxicity to estrogenic risk, particularly at low concentrations, and emphasize the potential threat to the male reproductive capacity of wildlife in bloom areas. Graphical abstract: Image 1 Highlights: Combined in vitro and in vivo assays were employed to reveal the underlying mechanism of the estrogenic potential of MC-LR. Environmental concentrations of MC-LR elicited estrogenic responses via disrupting steroidogenesis. The critical toxic threshold of MC-LR at the hormone and molecular level is between 1 and 30 μg/L. Abstract : MC-LR induced non-dose-dependent estrogenic effects via stimulating steroidogenesis in both in vitro and in vivo conditions.